Diversity of nonribosomal peptide synthetase and polyketide synthase gene clusters among taxonomically close Streptomyces strains - Hisayuki Komaki (Nature Portfolio, 2018)
Abstract To identify the species of butyrolactol-producing Streptomyces strain TP-A0882, whole genome-sequencing of three type strains in a close taxonomic relationship was performed. In silico DNA-DNA hybridization using the genome sequences suggested that Streptomyces sp. TP-A0882 is classified as Streptomyces diastaticus subsp. ardesiacus. Strain TP-A0882, S. diastaticus subsp. ardesiacus NBRC 15402T, Streptomyces coelicoflavus NBRC 15399T, and Streptomyces rubrogriseus NBRC 15455T harbor at least 14, 14, 10, and 12 biosynthetic gene clusters (BGCs), respectively, coding for nonribosomal peptide synthetases (NRPSs) and polyketide synthases (PKSs). All 14 gene clusters were shared by S. diastaticus subsp. ardesiacus strains TP-A0882 and NBRC 15402T, while only four gene clusters were shared by the three distinct species. Although BGCs for bacteriocin, ectoine, indole, melanine, siderophores such as deferrioxamine, terpenes such as albaflavenone, hopene, carotenoid and geosmin are shared by the three species, many BGCs for secondary metabolites such as butyrolactone, lantipeptides, oligosaccharide, some terpenes are species-specific. These results indicate the possibility that strains belonging to the same species possess the same set of secondary metabolite-biosynthetic pathways, whereas strains belonging to distinct species have species-specific pathways, in addition to some common pathways, even if the strains are taxonomically close.